2016
DOI: 10.1155/2016/3650927
|View full text |Cite
|
Sign up to set email alerts
|

Personality Traits in College Students and Caregiving for a Relative with a Chronic Health Condition

Abstract: The purpose of this study was to investigate among college students the relationship between personality traits and willingness to care for a relative with a chronic health condition. 329 undergraduate students completed an online questionnaire. Hierarchical multiple regressions found that after controlling for demographics personality traits explained 10% of the variance in willingness to provide emotional care, 7% in instrumental care, and 7% in nursing care. Within these models, greater empathy was uniquely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…As expected, this study revealed that there is no relationship between neuroticism and the TEQ score, which is in line with findings of other studies [ 82 , 83 , 84 ]. Our results support the validity of the TEQ, as this scale was not designed to measure neurotic traits associated with sharing of emotional distress of other people.…”
Section: Discussionsupporting
confidence: 93%
“…As expected, this study revealed that there is no relationship between neuroticism and the TEQ score, which is in line with findings of other studies [ 82 , 83 , 84 ]. Our results support the validity of the TEQ, as this scale was not designed to measure neurotic traits associated with sharing of emotional distress of other people.…”
Section: Discussionsupporting
confidence: 93%
“…Because the sample was composed of informal caregivers, the empathy-altruism hypothesis may apply. That is, people with higher levels of empathy (the opposite of psychoticism) are more willing to help a family member suffering a health chronic condition (Trujillo Perrin, Elnasseh, Pierce, & Mickens, 2016). Finally, internal consistency for Sincerity was α = .47, slightly lower than in the original questionnaire (α = .59 -.65) or the Spanish version (α = .54).…”
Section: Discussionmentioning
confidence: 88%
“…Women traditionally assume a caregiver role more frequently than men, 2–4 but accounts of caregiver willingness between men and women varies in the literature. Wells 32 reported a greater willingness in men than women regarding caring for a spouse, while Trujillo et al 26 discovered females were more willing than males. The finding that men had greater caregiver willingness than women was speculated to result from men giving less thought to the demands caregiving could bring whereas women have more realistic expectations for caregiver burden 32 …”
Section: Antecedentsmentioning
confidence: 99%
“…Family members who possess an empathetic attitude toward another's suffering are more willing to become caregivers 25,26 (Figure 2). According to the empathy‐altruism hypothesis, observing a loved one in distress can elicit an empathetic response 27 .…”
Section: Defining Attributesmentioning
confidence: 99%